Play-based learning in the primary school - Briggs, Mary
Play is an essential part of learning and development for children and is an increasingly important aspect of creative approaches to teaching and learning in primary education. This book demonstrates the value of play in all its different forms as a highly effective medium for teaching and learning across the curriculum
Keywords: Education, Elementary; Play; Grundschule; Spiel